Factors Associated with Nurses’ Discharge Planning Implementation in Hospital Inpatient Wards - Cahyaningrum, Ika; Maemunah, Neni; Kondo, Katarina Winingsi (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2026)
Discharge planning is an important component of the nursing process, which affects continuity of care, patient compliance, and prevention of readmission to hospital. However, its implementation in inpatient wards has not been optimal. This study investigates factors related to nurses’ implementation of discharge planning in hospital inpatient wards. This study employed a cross-sectional correlational design. The research population consisted of all 78 nurses in the inpatient wards of Hospital X, with a sample of 39 nurses selected using simple random sampling. The study was conducted at Hospital X in Malang Regency from November 2024 to January 2025. Data on ward supervisor supervision and nurses’ discharge planning implementation were collected using questionnaires and analyzed with Spearman’s rank correlation. The results showed no significant relationship between nurses’ education level or length of service and discharge planning implementation (p-value > 0.05). However, there was a moderate relationship between ward supervisor supervision and nurses’ discharge planning implementation, with a correlation coefficient of 0.479 and p = 0.002. Hospital management is advised to regularly oversee supervision and plan ward head supervision to improve nurses’ performance, particularly in implementing discharge planning.